Synthesis, docking, pharmacokinetic prediction, and acetylcholinesterase inhibitory evaluation of N-(2-(piperidine-1-yl)ethyl)benzamide derivatives as potential anti-Alzheimer agents - Ahmad Mohammadi-Farani; Farzaneh Moradi; Amin Hosseini; Alireza Aliabadi (Research in Pharmaceutical Sciences)
Background and purpose: Alzheimer’s disease is the most common form of dementia and the sixth most common cause of death in the US according to the Alzheimer’s Association. As regards, to date, no effective treatments are available because of the multifactorial nature of the disease, therefore, a large body of recent research has been allocated to the design and development of multi-target-directed ligands that can become effective drug candidates. Experimental approach: A novel series of benzamide derivatives (5a-5l) containing piperidine core were synthesized in the current work. After identification of the chemical structures of the members of this series using 1H NMR, IR, and MS spectra, their anti-acetylcholinesterase activity was assessed by the Ellman᾽s test. Docking studies were also performed to investigate the binding mode and determine the interacting amino acids with the corresponding ligands. Finally, the pharmacokinetic (ADME parameters) of the most potent derivative (5d) was predicted and compared with donepezil. Findings/Results: Compound 5d possessing the fluorine atom substitution at position ortho was the most active compound in these series (IC50 = 13 ± 2.1 nM). This compound demonstrated superior activity than the reference drug donepezil (IC50 = 0.6 ± 0.05 µM). Molecular docking showed a significant hydrogen bonding of the carbonyl group of compounds 5d with tyrosine 121 into the active site of acetylcholinesterase. Fortunately, this compound showed better promising ADME properties than donepezil. Conclusion and implication: The benzamide derivatives introduced in this paper could be proposed as potential anti-acetylcholinesterase.